2013
DOI: 10.2478/bpasts-2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Monte-Carlo aided design of neutron shielding concretes

Abstract: Abstract. The process of design of building composites, like concrete is a complex one and involves many aspects like physical and mechanical properties, durability, shielding efficiency, costs of production and dismantlement etc. There are plenty of parameters to optimize and computer tools can help to choose the best solution. A computer aided design plays an important role nowadays. It becomes more accurate, faster and cheaper, so laboratories often apply computer simulation methods prior to field testing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is a numerical method of multiple sampling of a neutron history and the final result is obtained statistically. A simplified algorithm of the MC neutron transport simulation was presented by Tefelski et al [2]. The MC simulation in this research was performed using MCNP code on a geometry and Pu-Be neutron source as it was used in experiment.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a numerical method of multiple sampling of a neutron history and the final result is obtained statistically. A simplified algorithm of the MC neutron transport simulation was presented by Tefelski et al [2]. The MC simulation in this research was performed using MCNP code on a geometry and Pu-Be neutron source as it was used in experiment.…”
Section: Simulationsmentioning
confidence: 99%
“…Previous studies by Piotrowski et al [1] and Tefelski et al [2] based on computer simulations using MC method indicate that both the type of concrete (normal and heavy-weight) and its compressive strength have a significant effect on the shielding against neutron. The decrease in the dose is proportional to the strength, apparent increase of cement content and the associated mass of bound water as a result of its hydration.…”
Section: Introductionmentioning
confidence: 98%
“…Different are the results of studies made by Tefelski et al [6] who compared neutron shielding calculated using MCNP code for ordinary, heavy-weight barite and reinforced concrete and concluded that the worst concrete for this purpose is barite heavy-weight concrete as it is full of high elements with very small cross-sections for neutron capture. In the same research it was proved that neutron attenuation for borated concrete in comparison to heavy concrete is of one or two orders of magnitude, but this advantage of borated concretes is removed as they have been the most activated and their activation decrease in time has been the slowest.…”
Section: B-15 Frommentioning
confidence: 99%
“…In the case of shielding against high-energy photons (gamma radiation) the increase in concrete density by change of aggregate type, e.g., from a normal to a heavy-weight type, is sufficiently effective [12,13]. Protection against neutrons is a more complex and sophisticated task [14][15][16], because neutrons are no-charge particles travelling in straight lines and interacting only with atomic nuclei while passing through matter. Neither the electrons surrounding a nucleus (the atomic electron cloud) nor the electric field caused by a positively charged nucleus affect a neutron's flight.…”
Section: Introductionmentioning
confidence: 99%